Engineering extracellular vesicles for targeted therapeutics in cardiovascular disease - Fu, Enze; Pan, Kai; Li, Zongjin (Frontiers in Cardiovascular Medicine, 2024)
Extracellular vesicles (EVs) are nanosized particles secreted by cells that play crucial roles in intercellular communication, especially in the context of cardiovascular diseases (CVDs). These vesicles carry complex cargo, including proteins, lipids, and nucleic acids, that reflects the physiological or pathological state of their cells of origin. Multiomics analysis of cell-derived EVs has provided valuable insights into the molecular mechanisms underlying CVDs by identifying specific proteins and EV-bound targets involved in disease progression. Recent studies have demonstrated that engineered EVs, which are designed to carry specific therapeutic molecules or modified to enhance their targeting capabilities, hold promise for treating CVDs. Analysis of the EV proteome has been instrumental in identifying key proteins that can be targeted or modulated within these engineered vesicles. For example, proteins involved in inflammation, thrombosis, and cardiac remodeling have been identified as potential therapeutic targets. Furthermore, the engineering of EVs to increase their delivery to specific tissues, such as the myocardium, or to modulate their immunogenicity and therapeutic efficacy is an emerging area of research. By leveraging the insights gained from multiomics analyses, researchers are developing EV-based therapies that can selectively target pathological processes in CVDs, offering a novel and potentially more effective treatment strategy. This review integrates the core findings from EV multiomics analysis in the context of CVDs and highlights the potential of engineered EVs in therapeutic applications.